A unique application of the second order derivative of FTIR–ATR spectra for compositional analyses of natural rubber and polychloroprene rubber and their blends. (September 2017) - Manohar, N.; Jayaramudu, J.; Suchismita, S.; Rajkumar, K.; Babul Reddy, A.; Sadiku, E.R.; Priti, R.; Maurya, D.J.
Abstract: The present study explores the feasibility of using a mathematical enhancement, such as the second order derivative of FTIR-ATR spectra, for compositional analyses of natural rubber (NR), chloroprene rubber (CR) and their blends in carbon black-filled vulcanizates. The infrared spectra of natural rubber, polychoroprene rubber and their respective carbon black-filled vulcanizates were recorded by using FTIR-ATR on a germanium crystal. Subsequently, the second order derivative of the spectra was obtained for analysis. The important infrared bands for the identification of these materials were assigned, and compositional analyses of the blends were carried out by using the second order derivative spectra.